Investing in farmers through public–private–producer partnerships: Rural empowerment and agricultural development scaling-up initiative in Indonesia - Bogor, Siti Amanah; Suprehatin, Suprehatin; Iskandar, Elvira; Eugenia, Lani; Chaidirsyah, Ranny M. (Food and Agricultural Organization of the United Nations, 2021)
Investing in farmers through public-private-producer partnerships Rural Empowerment and Agricultural Development Scaling-up Initiative in Indonesia. Investing in farmers – or agriculture human capital – is crucial to addressing challenges in our agri-food systems. A global study carried out by the FAO Investment Centre and the International Food Research Institute, with support from the CGIAR Research Programme on Policies, Institutions and Markets and the FAO Research and Extension Unit, looks at agriculture human capital investments, from trends to promising initiatives. One of the nine featured case studies is the Rural Empowerment and Agricultural Development Scaling-up Initiative in Indonesia. This programme adds perspectives on investing in human capital in agriculture through public-private-producer partnerships, using lead farmers, cocoa doctors and farmer field schools. The case study shows that the training and coaching provided increased knowledge of and practical skills in cocoa farming, including technical skills, soft skills and empowerment, leading to better productivity and cocoa quality. The programme increased farmers’ confidence to take on new activities and sell a quality product. In addition, farmers developed group cooperation and decision-making skills, and group members learned communication, entrepreneurship and marketing skills. This publication is part of the Country Investment Highlights series under the FAO Investment Centre's Knowledge for Investment (K4I) programme.